Penerapan Model CIPP Dalam Evaluasi Kegiatan Sains Anak Usia Dini Melalui Eksperimen “Gunung Meletus” - Nabila Husna Simatupang; Ika Nadia; Fanny Zaskia Ramadhani; Faizia Syahralivia; Isti Rafa Marshanda; Shahira Afini Azzahra Azzahra (Jurnal Pena Pendidikan Dasar, 2025)
This study aimed to evaluate the implementation of early childhood science learning through a STEAM-based “Volcano Eruption” experiment using the CIPP evaluation model (Context, Input, Process, and Product). The study was conducted at TK Permata Jaya and focused on evaluating an experimental learning activity implemented for children in Group B. Data were collected through observation, interviews, questionnaires, and documentation, and were analyzed using a descriptive qualitative approach. The evaluation results indicate that the experimental activity was aligned with the early childhood education curriculum and the developmental needs of children. In terms of input, teacher readiness and the availability of learning media adequately supported the implementation of the activity. The learning process was conducted in a structured manner and successfully stimulated children’s interest and enthusiasm, although direct hands-on involvement was still limited. The product evaluation shows positive impacts on children’s cognitive, language, and artistic development. Overall, the STEAM-based “Volcano Eruption” experiment demonstrates good instructional performance as a science learning activity in early childhood education, with the need for further follow-up to enhance safe and guided exploratory experiences for children.